Photoluminescence Broadening Induced by Internal Electric Field Variations in Polar InGaN/GaN Quantum Wells - Nguyen Thi Phuong Loan; Phan Xuan Le; Phan Thi Minh Man (Indonesian Journal of Material Research, 2026)
This study investigates the influence of internal electric field modulation on photoluminescence (PL) broadening in polar InGaN/GaN quantum wells (QWs). By applying an external bias, the internal electric field is effectively controlled, allowing systematic evaluation of its role in spectral broadening. Photoluminescence and electro-reflectance measurements reveal that reducing the internal electric field leads to a noticeable narrowing of the PL linewidth. A theoretical model is developed to describe the relationship between electric field fluctuations and emission energy variation. The results indicate that stronger internal electric fields enhance the sensitivity of emission energy to local potential fluctuations, thereby increasing PL broadening. Additionally, a reduction in the Huang-Rhys factor is observed under decreased electric field conditions, suggesting weakened exciton-phonon coupling. These findings provide direct experimental evidence of the role of internal electric fields in PL broadening and offer a pathway for spectral control in III-nitride optoelectronic devices.